Steganography Patterned Indonesian Sentences Without Using Keys in Supporting the Industrial Revolution 4.0 - R. Fanry Siahaan; Endra, A.P Marpaung (Sean Institute, 2021)
Data security issues become very important when the computer has been used as a communication tool on a global network (internet). One method that is quite popular for securing data from irresponsible parties is text-based steganography, where confidential data or information is hidden or inserted into other text media so as not to arouse suspicion from other parties. The text insertion model used is a dictionary based on 1,918 words consisting of 7-word classes that correspond to sentence patterns in Indonesian. In this study, confidential information in the form of text was successfully disguised into sentence patterns in Indonesian. For input data whose bit length is 8 the average output bit length is 20%, for the input bit length of 80 the average output bit length is 79.16%, and for the input bit length of 640 bits, the average output bit length is 95.24%. The meaning of the sentence is not fully understood.